Pemetaan Potensi Wisata dan Perencanaan Pengembangan Desa Jarak Kec. Wonosalam, Kab. Jombang - Andilas, Devi Destiani; Wijaya, Serli; Setiawan, Rudy; Juniwati, Anik (Jurnal Ilmiah Pariwisata, 2020)
Since 2009, local government Jombang region assigned Jarak Village-Wonosalam as one of agrotourism destination in Mojowarno agropolitan area. Jarak Village has a lot tourism potential, but not mapped yet properly so it hasn’t develop yet. Furthermore, human respource quality in the village are low since the villager mostly just elementary school graduate and also lack of tourism knowledge. This is an exploratory descriptive study with aims to mapping the potency then develop it into unique tourism attraction/destination. The data were collected trough observation, interview and focus group discussion then processed using triangulation method. Descriptive analysis was applied and bring out 19 potential attraction in Jarak Village include natural attraction, man-made attraction and cultural attraction. Keywords :   Tourism Potential; Tourism Attraction; Agrotourism.